Adherence to Patient-Reported Symptom Monitoring and Subsequent Clinical Interventions for Patients With Multiple Myeloma in Outpatient Care: Longitudinal Observational Study - Jens Lehmann; Kelly M de Ligt; Stefanie Tipelius; Johannes M Giesinger; Monika Sztankay; Sandra Voigt; Lonneke V van de Poll-Franse; Gerhard Rumpold; Roman Weger; Ella Willenbacher; Wolfgang Willenbacher; Bernhard Holzner (JMIR Publications, 2023)
BackgroundThe use of software to monitor patient-reported outcome measures (PROMs) can improve outcomes for patients with cancer receiving anticancer therapy; however, evidence from applications used in routine clinical practice is lacking. ObjectiveWe aimed to investigate adherence to and patient perceptions of a weekly, web-based PROM symptom monitoring program in routine clinical practice for patients with Multiple Myeloma. Moreover, we aimed to capture how clinical alerts prompted by the system influenced clinical care. MethodsWe conducted a single-center longitudinal observational study to evaluate patient adherence to and perceptions of the PROM monitoring software in routine practice. Patients with Multiple Myeloma remotely completed weekly treatment-specific PROMs to monitor key symptoms via a dedicated web-based platform. Alarming symptoms triggered clinical alerts in the application for the treatment team, which could initiate clinical interventions. The primary outcomes were the web-based assessment completion rate and patients' perceptions of the monitoring program, as assessed by an evaluation questionnaire. Moreover, clinical alerts prompted by the system and consequential clinical interventions were analyzed. ResultsBetween July 2021 and June 2022, a total of 55 patients were approached for participation; 39 patients participated (24, 61% male, mean age 63.2, SD 9.2 years). The median assessment completion rate out of all weekly scheduled assessments was 70.3% (IQR 41.2%-89.6%). Most patients (77%) felt that the health care team was better informed about their health status due to the web-based assessments. Clinical alerts were triggered for 1758 of 14,639 (12%) reported symptoms. For 548 of 1758 (31.2%) alerts, the symptom had been registered before and no further action was required; for 348 of 1758 (19.9%) alerts, telephone consultation and self-management advice sufficed. Higher-level interventions were seldom needed in response to alerts: referral to a doctor or specialist (88/1758, 5% alerts), medication changes (22/1758, 1.3%), scheduling additional diagnostics (9/1758, 0.5%), or unplanned emergency visits (7/1758, 0.4%). Most patients (55%) reported the calls in response to alerts gave them "quite a bit" or "very much" of an added feeling of security during therapy. ConclusionsOur study shows that high adherence to regular and tailored PROM monitoring can be achieved in routine clinical care. The findings provide valuable insight into how the PROM monitoring program and the clinical alerts and resulting interventions shaped clinical practice. Trial RegistrationClinicalTrials.gov NCT05036863; https://clinicaltrials.gov/study/NCT05036863